Oxidized Low-density Lipoprotein Associates Strongly with Carboxy-terminal Domain of Tissue Factor Pathway Inhibitor and Reduces the Catalytic Activity of the Protein - Horie, Shuichi; Hiraishi, Sayuri; Hamuro, Tsutomu; Kamikubo, Yu-ichi; Matsuda, Juzo (Thrombosis and Haemostasis, 2002)
Tissue factor pathway inhibitor (TFPI) is a physiological protease inhibitor of the extrinsic blood coagulation pathway. Previously we have shown that TFPI associates quite rapidly with oxidized lowdensity lipoprotein (ox-LDL), with a reduction of the inhibitory activity on factor X activation. In the present study, it was found, by means of agarose gel electrophoresis, that the pre-incubation of full-length rTFPI with heparin or the carboxy (C)-terminal part (peptide 240-265) of TFPI prevented the association with ox-LDL in a dose-dependent manner. When rTFPI lacking the C-terminal basic part of the molecule (rTFPI-C) was mixed with ox-LDL, only a small amount of rTFPI-C was shifted to the position of ox-LDL on electrophoresis. Further, ox-LDL did not reduce the activity of rTFPI-C. These results indicate that the C-terminal domain of TFPI molecule plays a predominant role in the binding to ox-LDL and the binding through the C-terminal part is essential for the ox-LDL-dependent reduction of the anticoagulant activity of TFPI.
Keywords: Tissue factor pathway inhibitor; oxidized low-density lipoprotein; factor Xa generation; heparin; atherosclerosis